Demographic characteristics and clinical profile of poor responders in IVF / ICSI: A comparative study - Nabaneeta Padhy; Shalu Gupta; Asmita Mahla; M Latha; Thangam Varma (Wolters Kluwer Medknow Publications, 2010)
Background: Ovarian response varies considerably among individuals and depends on various factors. Poor response in IVF yields lesser oocytes and is associated with poorer pregnancy perspective. Cycle cancellation due to poor response is frustrating for both clinician and the patient. Studies have shown that women conceiving after poor ovarian response have more pregnancy complications like PIH and preeclampsia than women with normal ovarian response. In addition, poor ovarian response could be a predictor of early menopause. This paper studies various demographic and clinical profiles of poor responders and tries to look at the known and unknown factors which could contribute to poor ovarian response in IVF. Materials and Methods: Data were collected retrospectively from 104 poor responders who had less than four oocytes at retrieval and compared with 324 good responders for factors like age, BMI, type of sub fertility, duration of sub fertility, environmental factors like stress at work, smoking, pelvic surgery, chronic medical disorder, indication of IVF, basal FSH, mean age of menopause in their mothers etc. Results: Among the poor responders, 60.57% were above 35 years of age compared to 36.41% in control group, which is statistically significant. Mean age of menopause in mother was found to be four years earlier in poor responder group. Male factor and unexplained infertility were significantly (P<0.05) higher in good responders (P<0.05). Significant proportion (31.73%) of women in study group had undergone some pelvic surgery (P<0.05). Conclusion: Apart from age, prior pelvic surgery also could be used as predictors for poor ovarian response. Heredity also plays a major role in determining ovarian response.